Pharmaceutical Terminology in Latin: Trivial Names of Medicinal Substances (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Pharmaceutical terminology plays a crucial role in ensuring the effective and safe use of medicinal substances by standardizing their nomenclature based on chemical structure, sources, and pharmacological effects. This study examines the classification of medicinal substances into natural and synthetic sources, highlights the significance of International Nonproprietary Names (INN), and compares trivial names with their official counterparts. The findings emphasize the necessity of precise naming in pharmaceutical practice to enhance drug safety and clinical applications.